2019
DOI: 10.3390/su11143840
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consumers’ Purchasing Behavior for Certified Aquaculture Products in South Korea

Abstract: This study aims to investigate consumers' decision-making process for purchasing certified aquaculture products using the theory of the planned behavior (TPB) model. Based on the TPB model, this study empirically examines the relationship among TPB constructs, namely; attitude, social norm, perceived behavioral control, and behavioral intention to purchase sustainably produced products (i.e., Aquaculture Stewardship Council-certified products). Data from a web-based survey conducted through an online survey co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…The DTPB has become one of the most utilised theories in explaining and predicting behaviours of individuals by decomposing a smaller construct in each belief (attitudinal, norm, control). Besides that, the DTPB is used to explain and predict intentions and behaviours in various research fields, such as consumer behaviour [15], web usage [16], usage intention [17], user intention [18], mobile application [19], M-commerce [20], utilitarian green products and hedonic green products [21], behavioural intention towards electric vehicles [22,23], behavioural intention towards certified aquaculture products [24], and green consumption [25].…”
Section: Introductionmentioning
confidence: 99%
“…The DTPB has become one of the most utilised theories in explaining and predicting behaviours of individuals by decomposing a smaller construct in each belief (attitudinal, norm, control). Besides that, the DTPB is used to explain and predict intentions and behaviours in various research fields, such as consumer behaviour [15], web usage [16], usage intention [17], user intention [18], mobile application [19], M-commerce [20], utilitarian green products and hedonic green products [21], behavioural intention towards electric vehicles [22,23], behavioural intention towards certified aquaculture products [24], and green consumption [25].…”
Section: Introductionmentioning
confidence: 99%
“…All of these attributes are not considered by the consumer in the study area and outside. Studies in Europe and South Korea showed a positive relationship between consumer attitude towards fishery products with certified eco-labels (Zander and Feucht, 2018;Yi, 2019). The mud crab fishers, mud crab brokers, and local consumers in the study site, for example, do not consider sustainable fisheries management principles.…”
Section: Social-economy Dpsir Framework For Mud Crab Fisherymentioning
confidence: 88%
“…For others, it was a tool for observing differences in fish consumption behaviour before and after nutrition education intervention (Mahumudiono et al, 2020) or for measuring the success of an advertising campaign for fresh fish (Scholderer, Grunert, 2001). To the best of the authors' knowledge, there are not many studies (Yi, 2019) that have applied this theory to farmed fish. Therefore, this research should make a valuable contribution to the scarce scientific data.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%